Occupations observatory - methodological note - Beblavy, Miroslav; Akgüc, Mehtap; Fabo, Brian; Lenaerts, Karolien (Brussels, 2016)
"As a result of technological progress and economic change, many new occupations have emerged in the labour market, while others have become redundant and disappeared. Along with these new and emerging occupations, new skills have been introduced that can be developed through formal education, on-the-job training or learning-by-doing (or in some other way). This paper presents the Occupations Observatory, which we have created with the aim of providing up-to-date information on these changes in the labour market – reflected in the rise of new occupations and their corresponding skill changes – to policy-makers, researchers, educational institutes, job seekers and many other stakeholders (and how occupational dynamics feed into the occupational classification schemes). We focus not only on new occupations that did not exist before but also on new occupations in terms of recognition, awareness and importance.